2023
DOI: 10.3390/jcm12237426
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Layer Spectral CT as Innovative Imaging Guidance in Lung Biopsies: Could Color-Coded Z-Effective Images Allow More Diagnostic Samplings and Biomarkers Information?

Filippo Piacentino,
Federico Fontana,
Giada Zorzetto
et al.

Abstract: The aim of the study was to try to obtain more information on diagnostic samplings and biomarkers using dual-layer spectral CT in lung biopsies. Lung biopsies were performed by merging images obtained with CBCT with those from spectral CT to use them as functional guidance, experimenting with double sampling to determine the difference between the area with a higher Z-effective number and that with a lower Z-effective number. Ten patients with large lung lesions on spectral CT were selected and underwent percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Chen et al ( 10 ) showed that in invasive colorectal adenocarcinoma, higher Zeff may be attributed to increased tumor heterogeneity, where the tumor tissue exhibited nuclear pleomorphism and abnormal elemental composition. In contrast, regions with lower Zeff imply the likelihood of less densely populated cellular structures or elements with lower atomic numbers ( 30 ). We believe that the standardized effective atomic number can better reflect the heterogeneity between HCC and may provide new markers for assessing poorly differentiated HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 10 ) showed that in invasive colorectal adenocarcinoma, higher Zeff may be attributed to increased tumor heterogeneity, where the tumor tissue exhibited nuclear pleomorphism and abnormal elemental composition. In contrast, regions with lower Zeff imply the likelihood of less densely populated cellular structures or elements with lower atomic numbers ( 30 ). We believe that the standardized effective atomic number can better reflect the heterogeneity between HCC and may provide new markers for assessing poorly differentiated HCC.…”
Section: Discussionmentioning
confidence: 99%